The bagging of Annona crassiflora fruits to control fruit borers - doi: 10.4025/actasciagron.v34i3.14713 - Germano Leao Demolin Leite; Manoel Ferreira Souza; Patrícia Nery Silva Souza; Márcia Michelle Fonseca; José Cola Zanuncio (Acta Scientiarum. Agronomy, 2011)
The objective of this work was to evaluate the use of plastic bags to protect the fruits of Annona crassiflora (Annonaceae) against Cerconota sp. (Lepidoptera: Oecophoridae). As protection against this fruit-boring insect, 100 fruits were enclosed in plastic bags. Another 100 fruits were not bagged. The fruits were selected from the following five ranges of diameters: 1 = 0.5 – 1.99; 2 = 2.00 – 3.99; 3 = 4.00 – 7.90; 4 = 8.00 – 11.90; and 5 = 12.00 – 16.00 cm. The bagged fruits of various diameters were attacked less frequently by the pest. The bagged fruits with a diameter of less than two cm were not attacked. The percentage of fruits attacked and the number of larvae/fruit increased as the diameter of fruits increased in both treatments. The bagged fruits initially less than two cm in diameter showed the greatest final diameter and height.